Cytomegalovirus disease in children with acute lymphoblastic leukemia. (18th May 2016) - Jain, Richa; Trehan, Amita; Mishra, Baijyantimala; Singh, Ramandeep; Saud, Bhuvan; Bansal, Deepak
ABSTRACT: Viral infections are an underrecognized problem in children on standard chemotherapy for acute lymphoblastic leukemia (ALL). In countries with high baseline seroprevalence of cytomegalovirus (CMV) such as India, it may be an important pathogen leading to fever, end-organ damage, and cytopenia. Data regarding the incidence and manifestations of CMV disease in pediatric ALL patients are scanty. The authors prospectively assessed all children on chemotherapy for ALL with prolonged febrile neutropenia (FN) for CMV disease over a 3-year period. Children with end-organ damage, including pneumonia, retinitis, and colitis, were also evaluated. Quantitative and qualitative polymerase chain reaction (PCR) from blood, body fluids, or tissue was done along with ophthalmologic evaluation. CMV disease was detected in 10% of the children with prolonged FN. In addition, other children were identified due to end-organ damage, lung and eye being the common organs of involvement. Time of CMV reactivation was essentially during nonintense phase of chemotherapy. Lymphopenia was present in most children, and prolonged lymphopenia was associated with relapse of CMV infection after therapy. The authors conclude that CMV is an important pathogen in children on standard chemotherapy for ALL. It has a good outcome with early detection and directed therapy. Parenteral ganciclovir is needed for a period of 14–21 days to prevent recurrence.